PfRH5 vaccine; from the bench to the vial - Philip Ilani; Prince B. Nyarko; Abdouramane Camara; Lucas N. Amenga-Etego; Yaw Aniweh (npj Vaccines)
Abstract The search for potent malaria vaccine candidate has seen several twists and turns. Here, we provide a perspective on the current state of PfRH5-based malaria vaccine development, the progress, existing challenges, and future research directions. We discuss the clinical trials in endemic regions, immune correlates of protection, prospects of integrating PfRH5 into multi-antigen vaccine strategies and considerations on the onward development/deployment of PfRH5 vaccine from the laboratory to endemic communities.